Work Loss and Mental Health during the COVID-19 Pandemic - Bernt Bratsberg; Anna Godøy; Rannveig Kaldager Hart; Oddbjørn Raaum; Bjørn-Atle Reme; Jonathan Wörn (Institute of Labor Economics (IZA), 2023)
We study the impact of work loss on mental health during the COVID-19 pandemic. Combining data on work loss and health care consultations from comprehensive individual-level register data, we define groups of employees delineated by industry, region, age, and gender. With these groups, we use a difference-in-differences framework to document significantly increased rates of consultations for psychological conditions among workers with higher exposure to work loss. The increases, and their persistence, were markedly higher for consultations in specialist (vs. primary) care, indicating that the deterioration of mental health was more than a widespread increase in lighter symptoms. Overall, our findings suggest that the economic disruptions of the COVID-19 pandemic adversely affected the mental health of workers most exposed to loss of work.
Keywords: I12; I14; I18; J65; 330; COVID-19; layoffs; work loss; job loss; mental health